Loss of FIC-1-mediated AMPylation activates the UPRER and upregulates cytosolic HSP70 chaperones to suppress polyglutamine toxicity. - Kate M Van Pelt; Matthias C Truttmann (PLoS Genetics)
Targeted regulation of cellular proteostasis machinery represents a promising strategy for the attenuation of pathological protein aggregation. Recent work suggests that the unfolded protein response in the endoplasmic reticulum (UPRER) directly regulates the aggregation and toxicity of expanded polyglutamine (polyQ) proteins. However, the mechanisms underlying this phenomenon remain poorly understood. In this study, we report that perturbing ER homeostasis in Caenorhabditis elegans through the depletion of either BiP ortholog, hsp-3 or hsp-4, causes developmental arrest in worms expressing aggregation-prone polyQ proteins. This phenotype is rescued by the genetic deletion of the conserved UPRER regulator, FIC-1. We demonstrate that the beneficial effects of fic-1 knock-out (KO) extend into adulthood, where the loss of FIC-1-mediated protein AMPylation in polyQ-expressing animals is sufficient to prevent declines in fitness and lifespan. We further show that loss of hsp-3 and hsp-4 leads to distinct, but complementary transcriptomic responses to ER stress involving all three UPRER stress sensors (IRE-1, PEK-1, and ATF-6). We identify the cytosolic HSP70 family chaperone F44E5.4, whose expression is increased in fic-1-deficient animals upon ER dysregulation, as a key effector suppressing polyQ toxicity. Over-expression of F44E5.4, but not other HSP70 family chaperones, is sufficient to rescue developmental arrest in polyQ-expressing embryos upon hsp-3 knock-down. We further show that knock-down of ire-1 or atf-6 blocks the upregulation of F44E5.4 in fic-1-deficient worms. Taken together, our findings support a model in which the loss of FIC-1-mediated AMPylation engages UPRER signaling to upregulate cytosolic chaperone activity in response to polyQ toxicity.